A definitive analytical spectroscopic study of Indian yellow, an ancient pigment used for dating purposes. (February 2017) - de Faria, Dalva L.A.; Edwards, Howell G.M.; Careaga, Valeria; Walt, Nicholas; Maier, Marta S.
Graphical abstract: Highlights: The Raman spectrum and NMR characterization of Indian yellow is reported. Tartrazine has been mistakenly reported as being that of Indian yellow. Indian yellow is highly luminescent and its Raman spectrum was obtained at 1064 nm. Abstract: The Raman spectrum of tartrazine has been mistakenly reported as being that of Indian yellow in the literature, which has serious consequences for the identification of this pigment in art works regarding their authentication. Unlike tartrazine, Indian yellow (a natural mixture of the magnesium and calcium salts of euxanthic acid) exhibits in its Raman spectrum a strong fluorescent background when visible excitation is used, however, excitation in the near infrared (1064 nm) permitted the observation of the Raman bands from the raw pigment with the main features placed at 1346, 1368, 1425, 1441 and 1626 cm −1 . Indian yellow identification was assured by 1 H and 13 C Nuclear Magnetic Resonance characterization and the complete assignment of the proton and carbon resonances was accomplished using heteronuclear single quantum correlation (HSQC), heteronuclear multiple bond correlation (HMBC), nuclear overhauser effect spectroscopy (NOESY) and 1 H– 1 H correlation spectroscopy (COSY). Scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) and X-ray fluorescence (XRF) analyzes were also conducted on a genuine sample of this historical pigment.